Basal Cell Carcinoma: Diagnostic and Therapeutic Management – Expert Opinion of the Polish Dermatological Society - Lesiak, Aleksandra; Szepietowski, Jacek; Czuwara, Joanna; Kamińska-Winciorek, Grażyna; Narbutt, Joanna; Reich, Adam; Kiprian, Dorota; Maj, Joanna; Owczarek, Witold; Owczarczyk-Saczonek, Agnieszka; Rudnicka, Lidia; Walecka, Irena; et al. (Dermatology Review/Przegląd Dermatologiczny, 2024)
The incidence of skin cancer continues to rise, presenting a significant epidemiological challenge for contemporary medicine. The most prevalent cancer in the Caucasian population is basal cell carcinoma. The gold standard for diagnosing skin cancers remains histopathological examination. However, for low-risk basal cell carcinoma subtypes, non-invasive imaging techniques may suffice to confirm the diagnosis, particularly prior to planned topical or destructive therapies. The guidelines below outline the clinical and pathomorphological subtypes of basal cell carcinoma, its dermoscopic characteristics, staging, and the available options for treatment and prevention of recurrence. The primary and preferred treatment method is the surgical removal of the lesion. The remaining non-surgical methods have lower cure rates and should therefore be reserved for cases with a low risk of recurrence, when surgery is contraindicated or not feasible.